2014
DOI: 10.3390/f5123070
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Maintaining Upland Forest Habitat Surrounding Salamander Breeding Ponds: Case Study of the Eastern Tiger Salamander in New York, USA

Abstract: Most amphibians use both wetland and upland habitats, but the extent of their movement in forested habitats is poorly known. We used radiotelemetry to observe the movements of adult and juvenile eastern tiger salamanders over a 4-year period. Females tended to move farther from the breeding ponds into upland forested habitat than males, while the distance a juvenile moved appeared to be related to body size, with the largest individuals moving as far as the adult females. Individuals chose refugia in native pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 56 publications
(128 reference statements)
0
20
0
Order By: Relevance
“…Tissue samples were collected from all four species between spring 2013 and summer 2014 (Table ). We collected all samples during the same breeding season to minimize the among‐year variation in breeding effort as most female ambystomatids do not breed annually (Semlitsch et al., ; Titus, Madison, & Green, ). When ponds were located within 100 m of each other, we pooled all individuals from those ponds into one group for downstream analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue samples were collected from all four species between spring 2013 and summer 2014 (Table ). We collected all samples during the same breeding season to minimize the among‐year variation in breeding effort as most female ambystomatids do not breed annually (Semlitsch et al., ; Titus, Madison, & Green, ). When ponds were located within 100 m of each other, we pooled all individuals from those ponds into one group for downstream analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Unisexual salamander post-breeding movement patterns were similar to other ambystomatids, characterized by long movements during emigration over a few nights followed by infrequent and shorter movements in their post-breeding home range ( Fig. 2; Williams, 1973;Madison, 1997;Titus et al, 2014). Unisexual salamanders moved as far as 463 m from the pool.…”
Section: Discussionmentioning
confidence: 57%
“…After realizing that we might bias movement by placing the animals on one side of the drift fence, we released the salamanders back into the vernal pools in 2014. We extended our 2013 telemetry season from 42 days (battery life of one transmitter) to 92 days by replacing transmitters in six animals (after McDonough and Paton, 2007;Titus et al, 2014). Unfortunately, the skin was weak at the site of the original incision, and we found two animals with an open incision 7 and 12 days after the second reimplant surgery.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the recent decline or eradication of these keystone species in the Sandhills, A. mavortium now largely rely on anthropogenic water sources, such as livestock ponds, which are less than 100 years old (DMF personal communication). In addition, some studies have found that Ambystoma rarely disperse over ~500 m (Titus, Madison, & Green, ), while others suggest much further dispersal distances, particularly when estimated by genetic methods (~1–6 km; Zamudio & Wieczorek, ; Peterman et al, ; Smith & Green, ; Denton et al, ). Ponds colonized by Ambystoma in our study area are relatively far apart, (mean = 1,817 m (1,048–4,456 m); Figure ), and it remains unknown how often individuals disperse between ponds.…”
Section: Methodsmentioning
confidence: 99%
“…Two ponds occur proximate to ponds 1 and 2 (that lack Ambystoma), and thus, this individual may have migrated between ponds in a step-wise manner. Alternatively, many studies have found that between-pond dispersal is more likely in recently metamorphosed juveniles, rather than adults, because adults with high philopatry possess a selective advantage due to the high costs of interpond dispersal (Dole, 1971;Gamble, McGarigal, & Compton, 2007;Gill, 1978;Rothermel, 2004;Semlitsch, 2008;Titus, Madison et al, 2014). Many studies do not test for sibling relationships between adult specimens because the probability of sampling adult siblings is very low when Ne is high (Peterman, Brocato, et al, 2016), but in systems with low Ne, testing for adult familial relationships may complement current understanding of dispersal and connectivity.…”
Section: Implications For Pond-breeding Amphibian Conservationmentioning
confidence: 99%